Pengaruh Pengawasan dan Komitmen Kerja Terhadap Kinerja Karyawan di Hotel Tentrem Yogyakarta - Icha Rizal; Feri Ferdian; Fran Serano Andres (Departemen Pariwisata Universitas Negeri Padang, 2026)
The objective of this study is to examine the impact of supervision and work commitment on employee performance at Hotel Tentrem Yogyakarta. A quantitative reseacrh approach utilizing a survey method was employed. Data collection was concuted via questionnaires, with a sample consisting of 152 employees from Hotel Tentrem Yogyakarta. Descriptive analysis results indicate that the supervision variable falls into the very good category with a mean score of 4,30, the work commitment variable falls into the very good category with a mean score of 4,37, and the employee performance variable falls into the very good category with a mean score of 4,38. Data analysis involved descriptive statistics, instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing-specifically the T-test, F test, and the measurement of the coefficient of determination (